The Biocontrol and Plant Growth-Promoting Properties of Streptomyces alfalfae XN-04 Revealed by Functional and Genomic Analysis - Chen, Jing; Hu, Lifang; Chen, Na; Jia, Ruimin; Ma, Qing; Wang, Yang (Frontiers in Microbiology, 2021)
Fusarium wilt of cotton, caused by the pathogenic fungal Fusarium oxysporum f. sp. vasinfectum (Fov), is a devastating disease of cotton, dramatically affecting cotton production and quality. With the increase of pathogen resistance, controlling Fusarium wilt disease has become a significant challenge. Biocontrol agents (BCAs) can be used as an additional solution to traditional crop breeding and chemical control. In this study, an actinomycete with high inhibitory activity against Fov was isolated from rhizosphere soil and identified as Streptomyces alfalfae based on phylogenetic analyses. Next, an integrative approach combining genome mining and metabolites detection was applied to decipher the significant biocontrol and plant growth-promoting properties of XN-04. Bioinformatic analysis and bioassays revealed that the antagonistic activity of XN-04 against Fov was associated with the production of various extracellular hydrolytic enzymes and diffusible antifungal metabolites. Genome analysis revealed that XN-04 harbors 34 secondary metabolite biosynthesis gene clusters (BGCs). The ability of XN-04 to promote plant growth was correlated with an extensive set of genes involved in indoleacetic acid (IAA) biosynthesis, 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase activity, phosphate solubilization, and iron metabolism. Colonization experiments indicated that EGFP-labeled XN-04 had accumulated on the maturation zones of cotton roots. These results suggest that S. alfalfae XN-04 could be a multifunctional BCA and biofertilizer used in agriculture.